Challenges in orphan drug development and regulatory policy in China. Issue 1 (December 2017) - Cheng, Alice; Xie, Zhi
Abstract While regulatory policy is well defined for orphan drug development in the United States and Europe, rare disease policy in China is still evolving. Many Chinese patients currently pay out of pocket for international treatments that are not yet approved in China. The lack of a clear definition and therefore regulatory approval process for rare diseases has, until now, de-incentivized pharmaceutical companies to pursue rare disease drug development in China. In turn, many grassroots movements have begun to support rare disease patients and facilitate drug discovery through research. Recently, the Chinese FDA set new regulatory guidelines for drugs being developed in China, including an expedited review process for life-saving treatments. In this review, we discuss the effects of these new policy changes on and suggest potential solutions to innovate orphan drug development in China.